Factors influencing the consumer behavior of Russian citizens towards luxury goods - Babenkova, Maria; Zlatić, Marija; Escobar Rios, Andrea; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2021)
This study aims to identify the main factors influencing the luxury goods consumption of the Russian sample group, following the method of PRECON developed by Deeter-Schmelz et al. (2000). The study utilizes factor analysis, with various tests such as the Keyser-Meyer-Olkin sampling of adequacy and the Cronbach alpha tests for internal consistency to test the factor analysis for reliability. The findings conclude with the sample group of 176 people displaying symptoms of the bandwagon effect, as well as the perfectionist effect. This is due to the factors with the most explained variance attending to the patron status, as well as the quality of the clothing, indicating a large amount of care for the way the owners are perceived when displaying the luxury items, as well as the quality of the items remaining high.
Vedoucí práce: Marija Zlatić
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2021
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2021
Způsob přístupu: Internet
Keywords: international business [obor bakal. práce]; bakalářské práce; bachelor's theses